(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
Birth time, President Ho Chi Minh was very interested in self-criticism and criticism. He believes that regular and serious implementation of self-criticism and criticism is the basic method to strengthen and develop unity and unity in the Party, self-criticism and criticism is also a sharp weapon to help for each cadre, party member promotes advantages and achievements, overcome, corrects shortcomings, mistakes and helps each other to progress; thereby improving revolutionary morality, to build the Party and build a clean government. Imbued with that thought, in the current period, our Party attaches great importance to and simultaneously performs the issue of self-criticism and criticism, considering this as one of the principles of organization and operation of The Party, which is the Party’s existence and development law, especially in the Party cell activities.